Decision-making process for gluing on footwear parts using AHP and statistics - Mares Castro, Armando (2023)
In manufacturing processes, there are conditions that continually impact decision-making among when choosing among alternatives; the selection is usually influenced by critical aspects such as quality, productivity, costs and customer feedback, among others. This article analyzes different adhesives for the process of gluing parts for sports shoes in a company located in the city of Purisima del Rincon in Guanajuato, México. The analysis employs statistical engineering tools and an Analytic Hierarchy Process (AHP) methodology. The case studied deals with an issue with gluing parts. The glue currently employed is of good quality but has drawbacks such as its high cost and thickness, which leads to a time-consuming manual application, affecting productivity. We propose and apply an AHP model with input information obtained by means of industrial experimentation in order to select the best alternative. Objective and subjective judgments relate to the quality score, production capacity, ease of application, and utility per pair. The chosen alternative represented the best option after factoring in all aspects of interest for the overall goal.